Effect Of Rice Bran Wax-Rice Bran Oil Oleogel On The Rheology, Texture And Thermal Properties Of Butter Cake - Roslee, Siti Rafeeqah Sh (Universiti Sains Malaysia, 2021)
The main objective of this research is to investigate the effect of different concentration of rice bran wax-rice brain oil (RBX-RBO) oleogel as a solid fat replacer on the rheological, thermal and textural properties of butter cake. The cake batter contained 100% margarine was considered as the control sample. All the oleogel samples were prepared by incorporating the rice bran wax (RBX) into rice bran oil (RBO) with the composition of 0.5 w/w%, 1 w/w%, 3 w/w% and 5 w/w%. This mixture was heated at 90°C followed by a rapid cooling process until 20°C with continuous stirring. This mixture was then mixed with other ingredients for butter cake production. All the batter showed shear-thinning behaviour as the viscosity decreased with increasing shear rate. The consistency coefficient of the RBX-RBO oleogel batter was significantly lower by 15.1 % than control sample. However, the consistency index of the batter increased up to 80.77% with increasing concentration of RBX-RBO oleogel. In all samples, the storage modulus G′ values were slightly higher than the loss modulus G′′ values, revealing the behavior of a soft gel. The solid fat replacement by RBX-RBO oleogel based batter changed the onset and peak temperature as well as enthalpy of gelatinization. The onset and peak temperature were significantly increased with increasing concentration of the oleogel. The qualities of the cake were measured through volume, texture and colour. Batter containing 0.5 w/w% of RBX-RBO oleogel is the most promising as solid fat replacement because its batter gave the lowest hardness value due to the higher specific volume value.